Case report: Primary Ewing sarcoma of the ureter, an exceptional finding of unique manifestation of disease - Valeri, Marina; Dore, Leocadia; Rudini, Noemi; Cieri, Miriam; Elefante, Grazia Maria; Saita, Alberto; Bertuzzi, Alexia; Colombo, Piergiuseppe (Frontiers in Oncology, 2023)
Ewing sarcoma (ES) is the second most common malignant bone tumor in children, also described in adults, with a highly aggressive behavior. ES belongs to the small round blue cell tumors family and presents the distinctive translocation of FET-ETS family genes (85% with EWSR1) generating gene fusions. Extraskeletal ES mainly occurs in soft tissues; urogenital tract is rarely affected, and ureteral localization is an exceptional event with only 4 cases described in the literature. Here we report the first Italian case of primary ES of the ureter, a 24-year-old young man with lower back pain and a narrowed left ureteral lumen at CT scan. ES of the urogenital tract is an almost unique condition with nonspecific clinical presentation and a challenging diagnosis for pathologists. We encourage awareness for these exceptional events in the differential diagnosis of ureteral lesions in young patients.